A Survey on Cannabinoid Treatment of Pediatric Epilepsy Among Neuropediatricians in Scandinavia and Germany - Klingenberg, Claus; Mouslet, George; Hjalgrim, Helle; Gerstner, Thorsten (Frontiers in Pediatrics, 2020)
Objectives: There is an increasing interest in cannabinoid-based products for the treatment of refractory pediatric epilepsy. However, a licensed cannabidiol (CBD) product was first approved for use by the European regulatory authorities in 2019. We aimed to obtain knowledge about clinical experience and attitudes towards cannabinoid use for epilepsy treatment among neuropediatricians in Scandinavia and Germany in the era before a CBD-product was commercially licensed and available. Study design: An internet-based questionnaire (Survey Monkey) was distributed by email to members of neuropediatric societies in Sweden, Germany, Denmark and Norway between February and April 2018. One reminder email was sent. Results: Eighty-six responded. Only 10 of 86 (12%) respondents had personal experience with off-label prescription of cannabinoid-based products, mainly for severe refractory pediatric epilepsies like Dravet syndrome and Lennox-Gastaut syndrome. However, 49 respondents (57%) had been exposed to relatives of patients that had requested or wanted to discuss cannabinoid therapy, and 32 (37%) respondents knew about cannabinoid self-medication. The knowledge regarding cannabinoid-based therapy among the respondents was overall limited. Main reasons for not prescribing cannabinoid-based therapy were concerns about law regulations and lack of an available product. Conclusion: Off-label cannabinoid-based therapy for pediatric epilepsy was not widely prescribed by neuropediatricians in Scandinavia and Germany in 2018.